Fulfillment of the Rights of Single Parent Male Children and the Legal Consequences of Hadhanah in West Tegal District - Evita Mardhotilah; Siti Maymanatun Nisa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Caring for and educating children must be done well by both parents, as long as the child is not mumayyiz or unable to take care of himself, even though his parents are divorced. This is a step for parents to guide and protect children so that a child is not neglected and their body, mind and religion are maintained. Parenting carried out by single male parents in West Tegal District is not easy, so it requires a second party to care for and educate children. The aim of this research is to analyze the fulfillment of the rights of single parent male children in West Tegal District and analyze the consequences of the hadhanah law for single male parents in West Tegal District. This research method uses empirical juridical with a legal sociology approach. The results of the research show that the fulfillment of the rights of children of single male parents in West Tegal District for some single male parents in fulfilling their children's rights after divorce is still not fulfilled. This is due to parents' obstacles in fulfilling their children's rights due to negligence, parents' economic limitations, lack of awareness of this matter, and parents' low education. The consequence of the hadhanah law for single male parents after divorce in West Tegal District is that the maintenance of children who have not yet mumayyiz falls on the mother. However, if a mother has died or is unable to care for and educate her child, then the right to care for the child falls to the father. The costs of maintaining the child are borne by the father. If parents or guardians neglect their responsibilities intentionally, then at the request of the relative concerned, the Religious Court can transfer the hadhanah rights to another relative who also has hadhanah rights. Then the legal consequences of carrying out Radha'ah in accordance with the provisions of Islamic law, giving rise to mahram because of the milk.